Impacts of Job Stress on Nurses Social Life: A study of Work Performance - Bibi, Hafiza Jaweria; Khanum, Sanober; Mushtaq, Rabia; Sikapuria, Zahra Karim (Pakistan Journal of Humanities and Social Sciences, 2023)
Nursing is a demanding and physically and emotionally challenging profession, and nurses are often exposed to high levels of job stress, which can have significant negative impacts on their physical and mental health, as well as their social life and work performance. This study aims to explore the impacts of job stress on the social life of nurses and how it affects their work performance in selected hospitals in Karachi. It is a cross-sectional study and data is collected from 100 nurses qualified with BS in Nursing and Diploma in General Nursing and Midwifery (DGNM) from SIUT, NICVD and Zia ud Din hospital by using a convenience sampling technique from October to December 2022. Results of the regression analysis show that the variable working long hours beta coefficient value of the regression table is .203 and the value of significance is 0.001; the variable work pressure beta coefficient value of the regression table is .213 and the value of significance is 0.001 and variable job stress beta coefficient value of regression table is .291 and value of significance is 0.000, which shows that these variables working long hours, work pressure and job stress has a significant impact on the nurses' social life and work performances. The study concluded that job stress and other associated factors hamper the work efficiency of nurses. Therefore, the present research study recommends that the management of the hospitals should ensure a stress-free environment at their workplace to create a better work-life balance for nurses to reduce stress levels and improve their overall well-being.